Transient performance of a magnetically geared induction machine. Issue 5 (16th July 2020) - Bidouche, Badr-El-Boudour; Lubin, Thierry; Mezani, Smaïl
Abstract : Purpose: The purpose of this paper is to investigate the transient performance of an induction machine coupled with a magnetic gear for industrial applications with low speed and high torque requirements. This new solution increases mechanical reliability and does not require maintenance and lubrication. The main objective is to study the direct-on-line starting ability of the electrical machine and its stability regarding a sudden change for the load torque. Design/methodology/approach: A nonlinear analytical model for the induction machine and the magnetic gear is first developed. The model is then linearized around an operating point to obtain the transfer function between the load angle and the electromagnetic torque from which an analytical expression for the mechanical resonant frequency is obtained. Findings: It is shown that the direct on-line starting is possible, if the moment of inertia of the load is not greater than a maximum value. Moreover, it is demonstrated that this new system present inherent overload protection. Originality/value: A new high-performance direct-on-line starting electrical machine is proposed to achieve high torque at low speed without mechanical gear to improve reliability and reduce maintenance.